Clinical Sports Medicine & Orthopedics - Hoffmann F; Heinz L; Mouton C; 2; Seil R; 2; 3; Nührenbörger C; 2 (Dynamic Media Sales Verlag, 2022)
Nonspecific lower back and buttock pain can significantly limit performance in athletes and can be of different origins. Sacral stress fractures are a rare and, in many cases, undiagnosed cause of lower back pain, which can lead to a substantial loss of time before a full return-to-sports is achieved with full athletic performance.The main risk factors of sacral stress fractures include repetitive full weight-bearing activities, short-term increases in exercise intensity or duration, and excessive energy deficit. Knowledge of the injury pattern, high clinical suspicion, and early MRI examination lead to a timely diagnosis. Therapeutically, load reduction with avoidance of high impact activities for at least 6 weeks is indicated initially, followed by dosed and progressive load increase. In parallel, supplementation with calcium and vitamin D is recommended. Athletes with recurrent stress fractures, regardless of region, should be evaluated for a Female Athlete Triad or its male counterpart, as well as endocrinologic risk factors. Preventive measures are possible for stress fractures but are not specific to sacral stress fractures.We describe two clinical case scenarios, one of a professional soccer player and one of an elite track and field athlete with sacral stress fractures as the cause of nonspecific lumbar pain.Key Words: Lower Back Pain, Sacrum, Football,Middle Distance Running